WEB MOBILE TECHNOLOGY APPLICATION FOR MARKET OPERATION - Galamiton, Narcisan S; Lumayag, Charisma G; Garcia, Jose Maria S; Malabago, Nolasco K; Suson, Roberto L (Journal of Agriculture and Technology Management, 2023)
Using different constructs and applications of the technology acceptance model (TAM), this research developed a web mobile technology application and determined its level of acceptability for market operation. The attributes of acceptability of the generated information system (IS) were analyzed using correlation. Findings revealed that web mobile technology application for the market operation was acceptable, user-friendly, and increased performance and productivity. In totality, the attributes of acceptability point out the quality of using the technology according to user-friendliness, providing convenience and comfort in seeking and deploying information leading to total productivity of the operations.